2021
DOI: 10.3390/brainsci11010087
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity Patterns of Deep Brain Stimulation Targets in Patients with Gilles de la Tourette Syndrome

Abstract: Since 1999, several targets for deep brain stimulation (DBS) in Gilles de la Tourette syndrome (GTS) have emerged showing similar success rates. Studies using different tractography techniques have identified connectivity profiles associated with a better outcome for individual targets. However, GTS patients might need individualized therapy. The objective of this study is to analyze the connectivity profile of different DBS targets for GTS. We identified standard target coordinates for the centromedian nucleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Therefore, the pvlGPi is also preferably chosen for DBS in TS patients with dystonic tics (67,85). Given its anatomical connections to sensorimotor regions, the modulation of these fibers seem like a probable mechanism of action for pvlGPi DBS (28,32). However, stimulation of projections from pvlGPi to sensorimotor networks was found to correlate negatively or not at all with tic improvement (31,131).…”
Section: Interpretation Of Main Findingsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, the pvlGPi is also preferably chosen for DBS in TS patients with dystonic tics (67,85). Given its anatomical connections to sensorimotor regions, the modulation of these fibers seem like a probable mechanism of action for pvlGPi DBS (28,32). However, stimulation of projections from pvlGPi to sensorimotor networks was found to correlate negatively or not at all with tic improvement (31,131).…”
Section: Interpretation Of Main Findingsmentioning
confidence: 99%
“…Identification of such connectivity patterns could potentially lead to the optimization of targets or discovery of new targets. Several studies have investigated structural connectivity patterns in DBS for TS (31,32,103,115,131,144). Importantly, studies showed that the VTA of the target alone did not predict the clinical efficacy of DBS for TS (103,145).…”
Section: Future Directions For Dbs Targeting In Tsmentioning
confidence: 99%
See 3 more Smart Citations